Cooligomerization of С9 fraction unsaturated hydrocarbons initiated by peroxides - Дзіняк, Богдан Остапович (Eastern-European Journal of Enterprise Technologies, 2014)
Today one of the ways of efficient use of ethylene production by-products, namely liquid pyrolysis products (LPP) of petroleum fractions is obtaining cooligomers - petropolymeric resins (PPR), used as substitutes for natural products in various industries. One method of industrial obtaining of PPR is cooligomerization of unsaturated hydrocarbons, contained in LPP fractions, initiated by organic peroxides. But at the same time, to obtain PPR with a satisfactory yield, considerable reaction time, increased concentration and dosed supply of initiator are needed. For increasing the PPR yield, it is expedient to raise the process temperature that requires using heat-resistant initiators, among which silicon peroxide compounds are of great interest. As a result of experimental studies, cooligomers from C9 fraction hydrocarbons of diesel fuel LPP using a number of heat-resistant organosilicon peroxides are obtained. The basic regularities of cooligomerization of C9 fraction unsaturated hydrocarbons, initiated by organosilicon peroxides are determined, the influence of the main factors (temperature, reaction time, nature and concentration of initiator) on the yield and physicochemical characteristics of the obtained cooligomers is defined. The relationship between the structure of peroxides and their effectiveness in the cooligomerization reaction is shown. The efficiency of using tris-tert-butylperoxy-vinylsilane, which provides increased raw materials hydrocarbons conversion and PPR yield is proved. Based on statistical analysis of the obtained results, regression equations are constructed and optimal technological parameters, which allow to obtain PPR with high yield, low color index and high bromine number value are selected. The obtained results are of practical interest in refining pyrolysis by-products for obtaining petropolymeric resins.